Workplace Bullying and Its Effects at A Higher Education Institution (HEI): Academics’ Perspectives - Sekgobela, Lebo; Matjie, Mokgata (International Journal of Qualitative Research, 2025)
This research explored workplace bullying (WB) among academic staff, recognizing its detrimental effects on mental health and job performance. The study aimed to understand the WB experienced by academic staff and its impact on their work effectiveness and to propose solutions. There is a significant gap in research regarding WB in academia, particularly affecting academic personnel. Using a qualitative exploratory design, the researchers accessed only six academic staff members conveniently, due to the sensitive nature of the study and conducted semi-structured interviews. Data were analyzed manually through thematic analysis and inductive coding. Findings revealed that workplace bullying is prevalent among junior and new academic staff members due to power abuse, due to junior and new staff powerlessness, inability to command respect, and due to their general lack of community and collegiality. Consequently, the presence of WB negatively affects the victims mentally leading to deteriorated job performance. The study underscores workplace bullying as a critical issue, affecting both employee welfare and organizational effectiveness. The HEI should implement mental well-being strategies, such as peer support systems, mentoring, and workshops on bullying in the workplace. The HEI has first-hand information about WB, its consequences, and how to prevent and minimize the effects through the WB policy development.